2019
DOI: 10.1002/asl.921
|View full text |Cite
|
Sign up to set email alerts
|

Collecting and utilising crowdsourced data for numerical weather prediction: Propositions from the meeting held in Copenhagen, 4–5 December 2018

Abstract: In December 2018, the Danish Meteorological Institute organised an international meeting on the subject of crowdsourced data in numerical weather prediction (NWP) and weather forecasting. The meeting, spanning 2 days, gathered experts on crowdsourced data from both meteorological institutes and universities from Europe and the United States. Scientific presentations highlighted a vast array of possibilities and progress being made globally. Subjects include data from vehicles, smartphones, and private weather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The different sources of data typically include recent measurements of precipitation and a previous forecast valid at the same time the measurements are made (Dance et al, 2019). The development of convection‐permitting NWP models has necessitated international research efforts in data assimilation over the past few years (Dance et al, 2019; Flack, Skinner, et al, 2019; Hintz et al, 2019). Unlike large‐scale models that rely on some form of parametrisation process to add in convective features, convection‐permitting NWP models can represent convective structures directly (Clark et al, 2016).…”
Section: Advances In Meteorological Monitoring and Forecastingmentioning
confidence: 99%
“…The different sources of data typically include recent measurements of precipitation and a previous forecast valid at the same time the measurements are made (Dance et al, 2019). The development of convection‐permitting NWP models has necessitated international research efforts in data assimilation over the past few years (Dance et al, 2019; Flack, Skinner, et al, 2019; Hintz et al, 2019). Unlike large‐scale models that rely on some form of parametrisation process to add in convective features, convection‐permitting NWP models can represent convective structures directly (Clark et al, 2016).…”
Section: Advances In Meteorological Monitoring and Forecastingmentioning
confidence: 99%
“…While uWx demonstrated that smartphone pressures could be retrieved frequently and efficiently, the quality of the observations remained poor. Since smartphone pressure sensors have biases which are systematic (Price et al ., 2018; Hintz et al ., 2019a), the primary source of uncertainty was attributed to location/elevation errors. This realisation facilitated a machine learning approach to predict and bias‐correct smartphone pressure errors, using only data from smartphone sensors and GPS.…”
Section: Crowd‐sourced Observations and Data Assimilationmentioning
confidence: 99%
“…Barometric pressure obtained via smartphones has been suggested by Mass and Madaus (2014) as a data source to improve forecasts of mesoscale phenomena. McNicholas and Mass (2018) and Hintz et al (2019a) assimilated smartphone pressure observations and found them to increase forecast skill. The Weather Observations Website (WOW) project is examining how to collect data from personal weather stations (PWS) as additional data (Met Office 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive overview of current crowdsourcing activities in NWP is given by Hintz et al (2019b), and Krennert et al (2018) give a more general overview of recent crowdsourcing activities within Europe.…”
Section: Introductionmentioning
confidence: 99%